Clinical Aspects of Dialysis Interventions: Physical and Sonographic Findings - Niyyar, Vandana Dua; Agarwal, Anil K.; Salman, Loay H. (Seminars in Interventional Radiology, 2022)
Physical examination (PE) of arteriovenous access remains of high clinical value and continues to be recommended by leading societies and guidelines. PE is easy to learn and perform. Once learned, examiners can provide a comprehensive arteriovenous (AV) access examination in 20 to 30 seconds. Therefore, we continue to advocate that AV access PE should be part of the training for all dialysis care providers. Similarly, ultrasound can provide important AV access evaluation and provide key information. It is relatively cheap and can be readily available at the bed side. Additionally, it is well accepted by patients, as it is not expected to be associated with pain or discomfort during the examination. We present in this review the key components of PE, signs and symptoms of AV access dysfunction, and the role of ultrasound in AV access evaluation as a complementary tool to PE.
Keywords: arteriovenous access; arteriovenous fistula; arteriovenous grant; AV access dysfunction; AV access physical examination; interventional radiology